2003
DOI: 10.1172/jci200317788
|View full text |Cite
|
Sign up to set email alerts
|

Antibody blockade of the Cripto CFC domain suppresses tumor cell growth in vivo

Abstract: Cripto, a cell surface-associated protein belonging to the EGF-CFC family of growth factor-like molecules, is overexpressed in many human solid tumors, including 70-80% of breast and colon tumors, yet how it promotes cell transformation is unclear. During embryogenesis, Cripto complexes with Alk4 via its unique cysteine-rich CFC domain to facilitate signaling by the TGF-β ligand Nodal. We report, for the first time to our knowledge, that Cripto can directly bind to another TGF-β ligand, Activin B, and that Cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
64
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 44 publications
3
64
1
1
Order By: Relevance
“…Interestingly, in addition to its obligate role as a Nodal/ GDF1/GDF3 coreceptor, Cripto can antagonize signaling by activins and TGF-β (13)(14)(15). GDF8/myostatin is a member of the TGF-β superfamily that has been implicated in the negative regulation of muscle growth and regeneration (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in addition to its obligate role as a Nodal/ GDF1/GDF3 coreceptor, Cripto can antagonize signaling by activins and TGF-β (13)(14)(15). GDF8/myostatin is a member of the TGF-β superfamily that has been implicated in the negative regulation of muscle growth and regeneration (36).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to its coreceptor function, Cripto is able to antagonize signaling of other members of the TGF-β family (i.e., activins and TGF-β). This inhibitory activity of Cripto results in a reduced ability to form an active ActRII/ActRIB receptor complex (13)(14)(15).…”
mentioning
confidence: 99%
“…Nodal may also be involved in regulating placental function since, in the rat, it has been suggested that Nodal may inhibit the differentiation of stem trophoblast cells into giant cells (11). Recently, Nodal mRNA has been detected in a number of cell lines originating from mouse mammary gland (34) and human ovary (35), suggesting that Nodal also plays a role in adult life. However, no functional studies have been reported on the role of Nodal in mammalian cells during adult life.…”
Section: Discussionmentioning
confidence: 99%
“…Activin is however antagonized by another secreted molecule, called Follistatin. There is also evidence that Cripto can inhibit signalling from Activin, TGF-b and Myostatin, which have in common to signal via Smad2/3 without requiring an EGF-CFC co-receptor to interact with their receptor complex [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%